Neuropsychosocial predictors of outcomes in opioid dependent patients post-detoxification - Ivers, Jo-Hanna (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2015)
The current treatment of choice for most opiate dependent persons is long term substitute prescribing. Detoxification is not an effective stand-alone treatment. Given the weak evidence base for detoxification coupled with the increased risk of overdose following a period of abstinence, many clinicians opt to continue substitute prescribing or indeed may dissuade opiate dependent persons from detoxifying.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin